Stroke death in patients receiving radiation for head and neck cancer in the modern era - Hardy, Sara J.; Bandyopadhyay, Sanjukta; Yang, Hongmei; Williams, Annalynn; Gudina, Abdi; Cummings, Michael A.; Zhang, Hong; Singh, Deepinder P.; Chen, Yuhchyau; Mohile, Nimish A.; Janelsins, Michelle C.; Milano, Michael T. (Frontiers in Oncology, 2023)
Objectives: Head and neck cancer is a common malignancy frequently treated with chemotherapy and radiotherapy. Studies have shown an increased risk of stroke with the receipt of radiotherapy, but data on stroke-related mortality are limited, particularly in the modern era. Evaluating stroke mortality related to radiotherapy is vital given the curative nature of head and neck cancer treatment and the need to understand the risk of severe stroke in this population. Methods: We analyzed the risk of stroke death among 122,362 patients (83,651 patients who received radiation and 38,711 patients who did not) with squamous cell carcinoma of the head and neck (HNSCC) diagnosed between 1973 and 2015 in the SEER database. Patients in radiation vs. no radiation groups were matched using propensity scores. Our primary hypothesis was that radiotherapy would increase the hazard of death from stroke. We also examined other factors impacting the hazard of stroke death, including whether radiotherapy was performed during the modern era when IMRT and modern stroke care were available as well as increased HPV-mediated cancers of the head and neck. We hypothesized that the hazard of stroke death would be less in the modern era. Results: There was an increased hazard of stroke-related death in the group receiving radiation therapy (HR 1.203, p = 0.006); however, this was a very small absolute increase, and the cumulative incidence function of stroke death was significantly reduced in the modern era (p < 0.001), cohorts with chemotherapy (p=0.003), males (p=0.002), younger cohorts (p<0.001) and subsites other than nasopharynx (p=0.025). Conclusions: While radiotherapy for head and neck cancer increases the hazard of stroke death, this is reduced in the modern era and remains a very small absolute risk.